Buccal Patches: A Comprehensive review - Prajapati, Shivani; Joshi, Aparna; Kumar, Kapil; Rajput, Vaishali; Ikram (International Journal of Indigenous Herbs and Drugs, 2023)
The buccal mucosa is one of the administration sites that might provide an alternative for peroral administration. The successful delivery of drugs across the oral mucosa represents a continuing challenge, as well as a great opportunity. Buccal delivery, has progressed far beyond the use of traditional dosage forms with novel approaches emerging continuously. Buccal drug delivery system in which drug enters directly in systemic circulation thereby by passing the first pass effect. This is painless and without discomfort, precise dosage form and facilitates ease of removal without significant associated pain. Moreover it shows better stability, patient compliance; uniform and sustained drug release and above all easy and cheap methods of preparation which can be done with various commonly available biocompatible polymers. The buccal  route has been researched for a wide variety of drugs and has gained significant attention and momentum since it offers remarkable advantages. Over past few decades, buccal route for systemic drug delivery using mucoadhesive polymers to significantly improve the performance of many drugs has been of profound interest. Present article deals with the different aspect of the buccal patches.